Constructive ergonomics - Falzon, Pierre, 1950- (CRC Press, Taylor & Francis Group, 2015)
"The goal for ergonomics has always been to adapt work, work environments, and machines to man. But is this goal still sufficient? Does it satisfy the needs of the individual, or of societies and organizations as they operate now? This book answers these questions. The goals of ergonomics should be the development of individuals, work situations, and construct know-how competences. This book proposes a new view on ergonomics where the goal of ergonomics is to eliminate the factors and conditions that impede performance and development"--Resumé vydavatele
Keywords: ergonomie; pracovní prostředí; human engineering; work environment; sborníky; papers of several authors